New Approaches to the Study of Marine Mammals - Romero, Aldemaro; Keith, Edward O. (IntechOpen, 2012)
The highly specialized nature of marine mammals when compared with their terrestrial counterparts, the environment in which they live, and the impact of humans on them throughout history and at the present, have made of the scholarship on these creatures something unique in itself. Therefore, it is not surprising that many researchers have also taken a distinctive approach to their study. This volume is aimed at providing a glimpse at such diversity of views and approaches while delivering valuable information on marine mammalogy. Given the increasing concerns regarding issues of anthropogenic factors affecting these animals, it is not surprising that the majority of chapters in this book deal with this subject.